Whole-exome sequencing identifies somatic mutations and intratumor heterogeneity in inflammatory breast cancer - Luo, Rui (NPJ Breast Cancer, 2021)
Inflammatory breast cancer (IBC) is the most aggressive form of breast cancer. Although it is a rare subtype, IBC is responsible for roughly 10% of breast cancer deaths. In order to obtain a better understanding of the genomic landscape and intratumor heterogeneity (ITH) in IBC, we conducted whole-exome sequencing of 16 tissue samples (12 tumor and four normal samples) from six hormone-receptor-positive IBC patients, analyzed somatic mutations and copy number aberrations, and inferred subclonal structures to demonstrate ITH. Our results showed that KMT2C was the most frequently mutated gene (42%, 5/12 samples), followed by HECTD1, LAMA3, FLG2, UGT2B4, STK33, BRCA2, ACP4, PIK3CA, and DNAH8 (all nine genes tied at 33% frequency, 4/12 samples). Our data indicated that PTEN and FBXW7 mutations may be considered driver gene mutations for IBC. We identified various subclonal structures and different levels of ITH between IBC patients, and mutations in the genes EIF4G3, IL12RB2, and PDE4B may potentially generate ITH in IBC.